Predictive Value of Serum Hepcidin Levels for the Risk of Incident End-Stage Kidney Disease in Patients with Chronic Kidney Disease: The KNOW-CKD - Sang Heon Suh; Tae Ryom Oh; Hong Sang Choi; Chang Seong Kim; Eun Hui Bae; Seong Kwon Ma; Kook-Hwan Oh; Kyu-Beck Lee; Ji Yong Jung; Soo Wan Kim (Karger Publishers, 2024)
Introduction: Despite the pivotal role of hepcidin in the development of anemia among the patients with chronic kidney disease (CKD), the association between serum hepcidin levels and CKD progression has been never investigated. We here hypothesized that elevation in serum hepcidin levels might be associated with the risk of incident end-stage kidney disease (ESKD) among the patients with pre-dialysis CKD. Methods: A total of 2,109 patients with pre-dialysis CKD at stages 1 to pre-dialysis 5 were categorized into the quartiles by serum hepcidin levels. The study outcome was incident ESKD. The median duration of follow-up was 7.9 years. Results: The analysis of the baseline characteristics revealed that unfavorable clinical features were in general associated with higher serum hepcidin levels. The cumulative incidence of ESKD was significantly differed by serum hepcidin levels, with the highest incidence in the 4th quartile (p < 0.001, by log-rank test). Cox regression analysis demonstrated that, compared to the 1st quartile, the risk of incident ESKD is significantly increased in the 4th quartile (adjusted hazard ratio 1.372, 95% confidence interval 1.070-1.759). Penalized spline curve analysis illustrated a linear, positive correlation between serum hepcidin levels and the risk of incident ESKD. Subgroup analyses revealed that the association is significantly more prominent in the patients with advanced CKD (i.e., estimated glomerular filtration rate <45 mL/min/1.73 m2). Conclusion: Elevation in serum hepcidin levels is significantly associated with the risk of incident ESKD among the patients with pre-dialysis CKD.